Numerical simulation of coherent effects under multiple scattering of linearly polarized light. - Kuzmin, Vladimir L.; Meglinski, I. V. (Springer Science Business Media, 2004)
The time correlation function and the interference component of the coherent backscattering from a multiple-scattering medium are calculated in the framework of the Monte Carlo technique. By comparing the stochastic Monte Carlo technique with the iteration procedure of solving the Bethe–Salpeter equation, it is shown that the simulation of the optical path of photon packets that have experienced n scattering events is exactly equivalent to calculating the nth-order ladder diagram. Using this equivalence, the Monte Carlo technique is generalized for simulation of the time correlation functions and coherent backscatteri